Symmetrical and Asymmetrical Interactions between Facial Expressions and Gender Information in Face Perception - Liu, Chengwei; Liu, Ying; Iqbal, Zahida; Li, Wenhui; Lv, Bo; Jiang, Zhongqing (Frontiers in Psychology, 2017)
To investigate the interaction between facial expressions and facial gender information during face perception, the present study matched the intensities of the two types of information in face images and then adopted the orthogonal condition of the Garner Paradigm to present the images to participants who were required to judge the gender and expression of the faces; the gender and expression presentations were varied orthogonally. Gender and expression processing displayed a mutual interaction. On the one hand, the judgment of angry expressions occurred faster when presented with male facial images; on the other hand, the classification of the female gender occurred faster when presented with a happy facial expression than when presented with an angry facial expression. According to the evoked-related potential (ERP) results, the expression classification was influenced by gender during the face structural processing stage (as indexed by N170) , which indicates the promotion or interference of facial gender with the coding of facial expression features. However, gender processing was affected by facial expressions in more stages, including the early (P1) and late (LPC) stages of perceptual processing, reflecting that emotional expression influences gender processing mainly by directing attention.